Amygdala Modulation During Emotion Regulation Training With fMRI-Based Neurofeedback - Barreiros, Ana Rita; Almeida, Inês; Baía, Bárbara Correia; Castelo-Branco, Miguel (Frontiers in Human Neuroscience, 2019)
Available evidence suggests that individuals can enhance the ability to modulate their brain activity in target regions within the Emotion Regulation network, using fMRI-based neurofeedback. However, there is no systematic review investigating the effectiveness of this method on amygdala modulation, a core region within this network. The major goal of this study was to systematically review and analyze the effects of real-time fMRI-Neurofeedback concerning neuromodulation of the amygdala during Emotion Regulation training. A search was performed in PubMed, Science Direct and Web of Science with the following key terms: «(“neurofeedback” or “neuro feedback” or “neuro-feedback”) and (“emotion regulation”) and (fMRI OR “functional magnetic resonance”)», and afterwards two additional searches were performed, replacing the term “emotion regulation” for “amygdala” and “neurofeedback” for “feedback”. From 531 identified articles, only 19 articles reported results of amygdala modulation during Emotional Regulation training through rtfMRI-NF using healthy participants or patients in original research articles. The results provide evidence for amygdala’s modulation during rtfMRI-NF training although studies’ heterogeneity precluded a quantitative meta-analysis – the included studies relied on different outcome measures to infer on success of neurofeedback intervention. Thus, a qualitative analysis was done instead. We identified as critical features influencing inference on the quality of the intervention the inclusion of a Practice-Run, a Transfer-Run and a Control-Group in the protocol, and to choose adequate Emotion Regulation strategies – in particular, the effective recall of autobiographic memories. Surprisingly, the Regulate versus Control Condition was lacking in most of the studies, precluding valid inference of amygdala neuromodulation within Session. The best controlled studies showed nevertheless positive effects. The type of stimulus/interface did not seem critical for amygdala modulation. We also identified potential effects of lateralization of amygdala responses following Up- or Down-Regulation, and the impact of fMRI parameters for data acquisition and analysis. Despite the qualitative evidence for amygdala modulation during rtfMRI-NF, there are still important limitations in the design of a clear conceptual framework of NF-training research. Future studies should focus on more homogeneous guidelines concerning design, protocol structure and, particularly, harmonized outcome measures to provide quantitative estimates of neuromodulatory effects in the amygdala.